SOSIOLOGI PENDIDIKAN SEBAGAI BASIS MANAJEMEN PENDIDIKAN DALAM PENGUATAN KARAKTER SISWA - Muhammad Yasin (Al-Rabwah, 2019)
Education is a tool that is believed to be able to build one's intelligence and personality for the better. But the problem is that if education only prioritizes intellectuality rather than the development of character and character of students, then the result is moral decadence or moral damage that ultimately causes violations of the social order of social values. implementation, the implementation of character education by using several ways, namely: through integration in all subjects, through the development of culture in the classroom and in the school environment So that character education in schools can run optimally, effectively, and efficiently, it requires effective and efficient management that is related to the needs of the community and the environment (social). This is because, character education in schools is an inseparable part of the school program. Of course, for the implementation to run well, it needs to be arranged and managed properly. It is here, then the management of character education in schools must be planned, organized by involving all stakeholders, the implementation, supervision and evaluation of the achievements of the character education program implemented.